Synthesis and Use of a Phosphonate Amidine to Generate an Anti‐Phosphoarginine‐Specific Antibody. (23rd November 2015) - Fuhrmann, Jakob; Subramanian, Venkataraman; Thompson, Paul R.
Abstract: Protein arginine phosphorylation is a post‐translational modification (PTM) that is important for bacterial growth and virulence. Despite its biological relevance, the intrinsic acid lability of phosphoarginine (pArg) has impaired studies of this novel PTM. Herein, we report for the first time the development of phosphonate amidines and sulfonate amidines as isosteres of pArg and then use these mimics as haptens to develop the first high‐affinity sequence independent anti‐pArg specific antibody. Employing this anti‐pArg antibody, we further showed that arginine phosphorylation is induced in Bacillus subtilis during oxidative stress. Overall, we expect this antibody to see widespread use in analyzing the biological significance of arginine phosphorylation. Additionally, the chemistry reported here will facilitate the generation of pArg mimetics as highly potent inhibitors of the enzymes that catalyze arginine phosphorylation/dephosphorylation. Abstract : Argininphosphorylierung : Die Synthese stabiler Phosphoarginin‐Analoga ermöglichte die Erzeugung von hochaffinen sequenzunabhängigen Antiphosphoarginin‐Antikörpern. Diese Antikörper können zum direkten Nachweis und zur Isolierung von Arginin‐phosphorylierten Proteinen eingesetzt werden.